2003
DOI: 10.1542/peds.112.6.1248
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Retinoblastoma: Presenting Signs as Prognosticators of Patient and Ocular Survival

Abstract: Most US children whose retinoblastoma is diagnosed initially present with leukocoria detected by a parent, despite routine pediatric screening for leukocoria via the red reflex test. Initial disease detection at the point of leukocoria or strabismus correlated with high patient survival rates and poor ocular survival rates for the presenting eye. Saving eyes and vision requires disease recognition before leukocoria, as demonstrated by the better ocular salvage rate among patients who had a positive family hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
5
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(156 citation statements)
references
References 21 publications
5
136
5
10
Order By: Relevance
“…The 5-year survival rate of retinoblastoma is 80% in Taiwan, which is lower than that reported in Europe (95%), 5 in the United States (493%), 14 and in Japan (10-year survival rate was 86.7% in bilateral cases and 92.3% in unilateral cases), 7 but close to that reported in Singapore (3-year survival rate was 83%). 6 In this study, all of the deaths occurred within the first 5 years after diagnosis, a finding consistent with data from Singapore.…”
Section: Discussionmentioning
confidence: 46%
“…The 5-year survival rate of retinoblastoma is 80% in Taiwan, which is lower than that reported in Europe (95%), 5 in the United States (493%), 14 and in Japan (10-year survival rate was 86.7% in bilateral cases and 92.3% in unilateral cases), 7 but close to that reported in Singapore (3-year survival rate was 83%). 6 In this study, all of the deaths occurred within the first 5 years after diagnosis, a finding consistent with data from Singapore.…”
Section: Discussionmentioning
confidence: 46%
“…In their series (only screened children) Imhof et al reported similar findings with more than 70% of their patients being diagnosed within the first 2 weeks of life and 82% being in the RE group I, II, or III. 2,4,5,11,12 Although patients in the I, II, or III group of the RE classification or in the A, B, or C group of the ICR are usually amenable to an eye conservation strategy (most often systemic chemotherapy combined with focal treatments), patients with more advanced disease (group IV, V and D, E) often require aggressive treatment such as enucleation or EBRT despite chemoreduction. 3,13 These results tend to suggest an association between intensive screening and early diagnosis, which probably explains the lower stages of the disease found in screened children.…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies have shown interesting results in terms of ocular conservation and final visual acuity (VA) in patients with positive family history screened early-in-life by fundus examinations at regular intervals and under general anaesthesia. 2,[4][5][6] Nevertheless, these were small uncontrolled studies with poorly defined screening schedules and included patients treated before the advent of chemotherapy as a first-line treatment for almost all familial RB patients.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in vascular density is common to most tumours, although there are some exceptions; pituitary tumours, for example, show higher intercapillary distances than the equivalent healthy tissue (Turner et al, 2000). In some tumours, such as retinoblastoma or nephroblastoma, vascular density is used as a criterion for prognosis (Abramson et al, 2003;Rössler et al, 2004) because of the higher risk of metastasis and better access of the tumour cells to nutrients and oxygen. Finally, it is important to point out that the mean vascular diameter of teratocarcinoma is about 2.4 times wider than in the normal testis.…”
Section: Discussionmentioning
confidence: 99%